Teachers Then and Now: Are They Truly Attuned to the Needs and Emotions of their Students? - Bishwokarma, Baburam (ILAM इलम, 2024)
Student-teacher relationship is crucial in the process of imparting quality education which requires teachers to understand the emotional needs, interests, and, realities of the students. This auto-hermeneutic study was carried out with an objective of finding whether the teachers in the past and now are aware of the emotional needs, interests, and realities of the students in the context of Nepal. The study was conducted reflecting my own experiences as a school student, school teacher, and guardian of a school going boy. Analysing the three representative stories used as the primary information, the study concluded that there seems no substantial shift in the teachers’ attitudes and behavior in the Nepalese classrooms. Teachers appear to be insensitive regarding the emotional dynamics of teacher-student relationships in the Nepalese context. Thus, it is imperative to follow a holistic approach to teacher professional development that includes not only the transfer of content knowledge but also the cultivation of empathetic and emotionally aware educators.